2022
DOI: 10.22271/kheljournal.2022.v9.i4c.2589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plyometric training on repeated countermovement jump performance of collegiate athletes

Abstract: The goal of the present study was to find out the effect of plyometric training on repeated countermovement jump performance of collegiate athletes. A total of six variables of repeated countermovement jump, i.e., height (HT), take-off force (TOF), impact force (IF), maximum concentric power (MCP), peak speed (PS), and take-off speed (TOS), were selected to fulfil the objective of the study. A total of twenty (N=20) participants were randomly selected from a physical training centre of the Gwalior area of Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Many studies have examined the direct effect of plyometric training on CMJ jumping ability, ground reaction forces, isokinetic forces, take-off force, take-off velocity, power etc. (Borah & Sajwan, 2022;Correia et al, 2020;Ismail et al, 2014;Matavulj et al, 2001;Ramirez-Campillo et al, 2021;Stojanović et al, 2017), and reported their individual results and conclusions. However, very few studies have investigated the effect of plyometric training on the performance of the CMJ test in different training surface settings.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined the direct effect of plyometric training on CMJ jumping ability, ground reaction forces, isokinetic forces, take-off force, take-off velocity, power etc. (Borah & Sajwan, 2022;Correia et al, 2020;Ismail et al, 2014;Matavulj et al, 2001;Ramirez-Campillo et al, 2021;Stojanović et al, 2017), and reported their individual results and conclusions. However, very few studies have investigated the effect of plyometric training on the performance of the CMJ test in different training surface settings.…”
Section: Introductionmentioning
confidence: 99%